The Challenge of a Church Going into Liquidation. (November 2019) - de Groot, Kees
This article engages in the debate on religion in Europe and suggests a way of understanding that takes both discontinuities and continuities within the process of secularization into account. The central thesis is that institutional religion is not simply coming to an end in Western societies; rather, its assets and properties are being redistributed. Dutch Catholicism is presented as an example giving insights into the presence of religion in liquid modernity. The article concludes with a suggestion as to how the Church might respond to a situation where the secular world is taking over ecclesial initiatives.